Preferences for coaching strategies in a personalized virtual coach for emotional eaters: an explorative study - Dol, Aranka; van Strien, Tatjana; Velthuijsen, Hugo; van Gemert-Pijnen, Lisette; Bode, Christina (Frontiers in Psychology, 2023)
Objectives Emotional eating is recognized as a potential contributor to weight gain. Emotional eaters often hide their problems because of feelings of shame about their behaviour, making it challenging to provide them with the necessary support. The introduction of a virtual coach might offer a potential solution in assisting them. To find out whether emotional eaters are receptive to online personalized coaching, we presented emotional eaters with two essential proto-typical problem situations for emotional eaters: 'experiencing cravings' and 'after giving in to cravings,' and asked them whether they preferred one of the three coaching strategies presented: Validating, Focus-on-Change and Dialectical. Methods An experimental vignette study (2 x 3 design) was carried out. The vignettes featured two distinct personas, each representing one of the two common problem scenarios experienced by emotional eaters, along with three distinct coaching strategies for each scenario. To identify potential predictors for recognition of problem situations, questionnaires on emotional eating (DEBQ), personality traits (Big-5), well-being (PANAS), and BMI were administrated. Results A total of 62% of the respondents identified themselves with ‘after giving in to cravings’ and 47% with ‘experiencing cravings’. BMI, emotional eating and emotional stability appeared to be predictors in recognizing both the problem situations. In ‘experiencing cravings’, the participating women preferred Dialectical and the Validation coaching strategies. In the ‘after giving in to cravings’ condition, they revealed a preference for the Dialectical and the Focus-on-Change coaching strategies. Conclusions Using vignettes allowed a less threatening way of bringing up sensitive topics for emotional eaters. The personas representing the problem situations were reasonably well recognized. To further enhance this recognition, it is important for the design and content of the personas to be even more closely related to the typical problem scenarios of emotional eaters, rather than focusing on physical characteristics or social backgrounds. This way, users may be less distracted by these factors. With the knowledge gained about the predictors that may influence recognition of the problem situations, design for coaching can be more customized. The participants represented individuals with high emotional eating levels, enhancing external validity.